Pengaruh Strategi Bauran Pemasaran Terhadap Kepuasan Konsumen Pada Al-Hijrah Bakery & Cake Rantauprapat - Novita Azhari; Yuniman Zebua; Daslan Simanjuntak (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of product, price, place and promotion on consumer satisfaction at AL-Hijrah Bakery and Cake Rantauprapat. The sample in this research was 91 consumers of AL-Hijrah Bakery and Cake Rantauprapat. The method used in this research is a quantitative descriptive method. The results of the research stated that the Fcount value was 78.243 and the Sig value was 0.001. Meanwhile, the Ftable value used is the F distribution value with degrees of freedom df1 = (k-1) = (4-1) = (3) and df2 = (n-k) = (86) at α = 0.05, namely 2.71. Next, the Fcount value is compared with the Ftable value, so we get Fcount (78.243) > Ftable (2.71) and a significance level of 0.001 < 0.05. This shows that product, price, place and promotion together (simultaneously) influence consumer satisfaction. This means that the hypothesis can be accepted.